EFEKTIFITAS METODE GARDENING CLASS SEBAGAI MEDIA EDUKASI GIZI BAGI ANAK USIA DINI PADA PAUD DI KOTA KUPANG - Indriati Andolita Tedju Hinga (CHMK Applied Science Journal, 2019)
Children are a group that is vulnerable to the risk of malnutrition because most nutrients are used for growth and physical development. Unbalanced food consumption patterns are a major factor in nutrition problems. NTT is the province with the highest prevalence of malnutrition and stunting in Indonesia. Increased knowledge and awareness about nutrition can be done early through media-based nutrition education, one of which is the gardening class method. This study aims to determine the effectiveness of the gardening classes method to increase the knowledge and interest of children consuming vegetables and fruit at Fajar Kasih Preschool and Cinta Bangsa Preschool in Kupang City. The method used was pre-experiment with one-group pretest posttest research design. The sampling technique used was total sampling, namely 38 respondents. The data obtained were analyzed using paired-sample T-test. The results of this study indicate that the gardening classes method is effective in increasing the knowledge and interest of children consuming vegetables and fruits with a significance value (ρ)0.00<(α)0.05. Gardening class methods are highly recommended as one of the effective learning media in nutrition education for children. Keywords: Gardening Class, Nutrition Education Media, Children